NOVA DOENÇA DA FRUTEIRA DO CONDE CAUSA PELO NEMATÓIDE Rodopholus similis - Lordello, Luiz Gonzaga E.; Monteiro, Ailton Rocha; Suzuki, Oswaldo (REVISTA DE AGRICULTURA, 2015)
NOVA DOENÇA DA FRUTEIRA DO CONDE CAUSA PELO NEMATÓIDE Rodopholus similis